Additive‐Controlled Switchable Selectivity from Cyanobenzenes to 2‐Alkynylpyridines: Ruthenium(II)‐Catalyzed [2+2+2] Cycloadditions of Diynes and Alkynylnitriles. Issue 9 (10th April 2018) - Bhatt, Divya; Patel, Neha; Chowdhury, Hrishikesh; Bharatam, Prasad V.; Goswami, Avijit
Abstract: A highly efficient additive‐dependent chemoselective protocol for the synthesis of fused cyanoarenes and 2‐alkynylpyridines has been developed by the reaction of 1, 6‐diynes with alkynylnitriles using chloro(pentamethylcyclopentadienyl) (cyclooctadiyne)ruthenium(II) as catalyst in dimethoxyethane (DME). The course of the reaction can be drastically altered simply by adding a catalytic amount of AgOTf as an additive resulting in a comprehensive shift in product formation from cyanoarenes to 2‐alkynylpyridines. Theoretical studies clearly indicate that the neutral Ru‐complex is responsible for the formation of cyanobenzenes, whereas the in situ generated cationic Ru‐complex plays a crucial role in the 2‐alkynylpyridines formation. Abstract :